2007
DOI: 10.1188/07.cjon.659-666
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Rash Is It?: Deciphering the Dermatologic Toxicities of Biologic and Targeted Therapies

Abstract: An overwhelming number of new agents, including targeted agents with unique mechanisms of action, are available in oncology practice today. Along with the benefit of new treatments for patients comes the unfamiliarity of associated toxicities and learning the best methods to minimize side effects. One such toxicity has been the spectrum of dermatologic reactions from some of the newer small-molecule inhibitors and monoclonal antibodies. Scientific evidence describing the unique rashes and methodologies to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…128 An important part of the management plan is educating patients about the likelihood of developing dermatologic toxicity. One toxicity that can significantly affect quality of life is the development of HFSR/acral erythema.…”
Section: Strategies To Manage the Toxicities Of Targeted Agentsmentioning
confidence: 99%
“…128 An important part of the management plan is educating patients about the likelihood of developing dermatologic toxicity. One toxicity that can significantly affect quality of life is the development of HFSR/acral erythema.…”
Section: Strategies To Manage the Toxicities Of Targeted Agentsmentioning
confidence: 99%
“…The phase I-III studies that have thus far established MKIs, such as sorafenib, as effective therapeutic agents for metastatic cancers have not included the systematic study of HFSR management approaches [30,39,40]. Thus, a major conclusion from our study points to the need for additional research to test and compare the various recommendations for prevention and treatment of HFSR and to further elucidate the most efficacious methods for treating the side effects observed with newer targeted therapies [36]. Specifically, research is needed on: (a) appropriate patient education on prophylaxis for HFSR and its effects on patient outcomes; (b) how often the patient should be seen by an oncologist or dermatologist after beginning treatment with MKIs; (c) how to accurately diagnose HFSR in its mild forms and recognize subsequent dermatologic complications; (d) how to effectively treat and remove the calluses on hands and feet without leading to increased HFSR damage and symptom burden; (e) providing guidance to both patients and providers on the best types of gel inserts, cushions, and soft footwear; (f) identifying the treatment strategies that are most effective at each grade of toxicity or severity; and (g) testing the effectiveness of specific emollients and keratolytic creams for preemptive or reactive treatment of MKI-associated HFSR.…”
Section: Discussionmentioning
confidence: 97%
“…Our systematic review of the published literature through , revealed that current recommendations on the clinical approaches to HFSR prevention and treatment are largely anecdotal, derived from case reports, based on practices implemented during clinical trials to optimize MKI treatment duration, culled from postmarketing practices, or extrapolated from approaches used for chemotherapy-induced HFS (e.g., capecitabine, 5-fluorouracil , doxorubicin) rather than specifically from MKIs. The literature on treatment of HFS stemming from the use of chemotherapeutic agents and the current recommendations may or may not be appropriate in treating the side effects of newer agents [36]. Although HFSR in patients treated with MKIs may resemble the more commonly known presentation seen in patients receiving capecitabine, fluorouracil, or doxorubicin [4], when the condition is associated with MKI treatment it is thought to be a distinct entity [1,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations